Biomimetic co-assembled nanodrug of doxorubicin and berberine suppresses chemotherapy-exacerbated breast cancer metastasis. (April 2021) - Zheng, Xiao; Zhao, Yawei; Jia, Yong; Shao, Dan; Zhang, Fan; Sun, Madi; Dawulieti, Jianati; Hu, Hanze; Cui, Lianzhi; Pan, Yue; Yang, Chao; Sun, Wen; et al.
Abstract: Chemotherapy is a major approach for treating breast cancer patients. Paradoxically, it can also induce cancer progression. Understanding post-chemotherapy metastasis mechanism will help the development of new therapeutic strategies to ameliorate chemotherapy-induced cancer progression. In this study, we deciphered the role of HMGB1 in the regulation of TLR4-mediated epithelial to mesenchymal transitions (EMT) process on doxorubicin (Dox)-treated 4T1 breast cancer cells. Berberine (Ber), a clinically approved alkaloid has been demonstrated as an HMGB1-TLR4 axis regulator to Dox-exacerbated breast cancer metastasis in vitro and in vivo . Hypothesizing that combination of Dox and Ber would be beneficial for breast cancer chemotherapy, we engineered self-assembled nanodrug (DBNP) consisting of Dox and Ber without the aid of additional carriers. After cloaking with 4T1 cell membranes, DBNP@CM exhibited higher accumulation at tumor sites and prolonged blood circulation time in 4T1 orthotopic tumor-bearing mice than DBNP. Importantly, DBNP@CM not only effectively inhibited tumor growth with fewer side effects, but also remarkably suppressed pulmonary metastasis via blocking HMGB1-TLR4 axis. Together, our results have provided a promising combination strategy to dampen chemotherapy-exacerbated breast cancer metastasis and shed light on the development of biomimetic nanodrug for efficient and safe breast cancer chemotherapy.